Differences in nonmonetary value of ecosystem goods and services among Kalinago and Afro-Creole peoples of the commonwealth of dominica, West Indies - Rodríguez, L.C.; Portela, R.; Boumans, R. (2006)
Through time, interactions between physical and biotic factors contribute to emerging landscape patterns. The dynamics among social and cultural groups influence the human-mediated contribution to this process. This paper explores the cultural, historical, and socioeconomic differences among peoples as it could affect their recognition of the contribution of ecosystem goods and services provided by alternative land covers to the local well-being. Here, we present the results of a field study developed in the Commonwealth of Dominica among the native Kalinago and the Afro-Creole inhabitants. The results suggest that the two groups do not differ in their valuation of specific land covers but differ regarding ecosystem goods and services. Over the course of time, differences in preferences will have implications for the ecological trajectory of the island, according to the respective empowerment of the groups. Differences in the value of these services and their relationships with land covers are discussed based on predominant economic activities and constraints that categorize both groups.